Effects of Angiotensin-Converting Enzyme Inhibitors on Arterial Stiffness: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Xiuli Li; Peng Chang; Qiongying Wang; Hao Hu; Feng Bai; Ningyin Li; Jing Yu (Cardiovascular Therapeutics)
To determine the effects of ACEIs on arterial stiffness, a meta-analysis of randomized controlled trials was conducted. Relevant articles that investigated the effects of ACEIs on arterial stiffness from PubMed, Embase, and the Cochrane library from inception to September 2018 were systematically retrieved. The investigated outcomes included brachial-ankle pulse wave velocity (ba-PWV) and carotid-femoral PWV (cf-PWV) by using weighted mean differences (WMDs) and 95% confidence intervals (CIs) with the random-effects model. A total of 17 RCTs including 1,458 individuals were included. The summary results indicated no significant differences between ACEIs and control for ba-PWV and cf-PWV. Also, no significant differences between ACEI and control for ba-PWV and cf-PWV were observed in hypertensive patients, while the therapeutic effects of ACEI versus placebo showed statistically significant difference. Moreover, subgroup analysis indicated that the levels of ba-PWV were significantly associated if the study was conducted in Western countries, mean age <60.0 years, percentage male ≥60.0%, compared with ARBs, baseline PWV <10.0, and high-quality study. Furthermore, the significant levels of cf-PWV in patients who received ACEIs were observed when percentage male was ≥60.0% and the studies were of high-quality. Finally, no significant differences were observed between ACEIs and other antihypertensive drugs regarding the changes of systolic blood pressure (SBP) and diastolic blood pressure (DBP). The overall analysis suggested no significant differences between ACEIs and other antihypertensive drugs for ba-PWV and cf-PWV levels, whereas ACEIs versus placebo showed lower levels of ba-PWV and cf-PWV.